2013
DOI: 10.12816/0006044
|View full text |Cite
|
Sign up to set email alerts
|

Winter Hypertension : Potential Mechanisms

Abstract: Abstract:Hypertension exhibits a winter peak and summer trough in countries both north and south of the equator. A variety of explanations have been proposed to account for the seasonal nature of hypertension. It is likely that this reflects seasonal variations in risk factors. Seasonal variations have been demonstrated in a number of risk factors may play essential roles for seasonality of hypertension such as noradrenalin, catecholamine and vasopressin, vitamin D, and serum cholesterol. However, a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 82 publications
(47 reference statements)
0
16
0
4
Order By: Relevance
“…Pathophysiologically, this will happen due to an increase of intracellular calcium levels, resulting in endothelial and vascular growth dysfunction [75]. Population studies also support these theories [76-78]. Rostand [79] postulated that the farther a population is settled from the equatorial line, the higher its blood pressure will be, estimating that for every 10 degrees of distance, pressure will rise 2.5 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Pathophysiologically, this will happen due to an increase of intracellular calcium levels, resulting in endothelial and vascular growth dysfunction [75]. Population studies also support these theories [76-78]. Rostand [79] postulated that the farther a population is settled from the equatorial line, the higher its blood pressure will be, estimating that for every 10 degrees of distance, pressure will rise 2.5 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…That correlates with increased frequency of phrase "hypertension" searches in Google. The cause of higher BP during colder months is multifactorial [20]. Both systolic and diastolic BP rise when the temperature drops [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts should also be made to ensure that our lifestyles, in relation to diet, regular exercise, are at least as healthy in winter as they are in summer. [20] The strengths of the study were that seasonal variation in the prevalence of hypertension has not been studied much in India. Careful analysis of the data indicated that the variations in blood pressure attributable to the month of the year are at least as significant as those due to physiological variables.…”
Section: Discussionmentioning
confidence: 99%